2020
DOI: 10.1519/jsc.0000000000003798
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Growth Hormone Response to Anaerobic Exercise Among Children With Overweight and Obesity

Abstract: Hejla, D, Dror, N, Pantanowitz, M, Nemet, D, and Eliakim, A. Reduced growth hormone response to anaerobic exercise among children with overweight and obesity. J Strength Cond Res 36(8): 2194–2197, 2022—The aim of the present study was to examine the effect of an anaerobic exercise test on growth hormone (GH) secretion in children with overweight and obesity compared with children with normal weight. Fifteen children with overweight (body mass index percentile [BMI%ile] ≥85 < 95) and obesity (BMI%ile ≥95) and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…As exercise impacts many of the endocrine system's homeostatic functions, these interactions are especially important for the GH/IGF-I axis 39,40 . Exercise promotes anabolic components of the growth GH-IGF-axis in children 41 ; on the contrary, the typical increase in circulating GH seen in response to exercise would be attenuated in children with disease, such as ADHD 42 , overweight, and obesity 43 . As expected, our results revealed that different types of exercise can effectively improve GH and IGF-I level in children, such as physical activity, intellectual activity, physical combine with intellectual activity.…”
Section: Discussionmentioning
confidence: 99%
“…As exercise impacts many of the endocrine system's homeostatic functions, these interactions are especially important for the GH/IGF-I axis 39,40 . Exercise promotes anabolic components of the growth GH-IGF-axis in children 41 ; on the contrary, the typical increase in circulating GH seen in response to exercise would be attenuated in children with disease, such as ADHD 42 , overweight, and obesity 43 . As expected, our results revealed that different types of exercise can effectively improve GH and IGF-I level in children, such as physical activity, intellectual activity, physical combine with intellectual activity.…”
Section: Discussionmentioning
confidence: 99%
“…Physiologically, obesity has become a risk factor that may affect the release or regulation of growth hormones (Høgild et al, 2019). Hejla, Dror, Pantanowitz, Nemet, & Eliakim (2022) reported that GH secretion was lower in overweight and obese individuals than in normal weight individuals. The association of obese individuals with low growth hormone levels was also reported by Savastano, Di Somma, Barrea, & Colao (2014) Obesity causes a decrease in GH secretion, resulting in increased fat mass, decreased lipolysis, and decreased insulin sensitivity, leading to metabolic disorders (Høgild et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, research by Sasaki et al (2014) found no change in GH response after 4 weeks (3 days/week, 12 sessions total) of high-intensity interval training (10 sets of 1 min pedaling at 85% VO 2 max with a 30 s rest between sets) in sedentary men. In another case, research conducted by Hejla, Dror, Pantanowitz, Nemet, & Eliakim (2022) a single session of the Wingate anaerobic test (WAnT) with 10 bouts of 15-second cycling separated by 1 minute of rest significantly reduced GH levels in children with overweight and obesity compared with those with normal weight. Meanwhile, a study by Deemer et al (2018) used a crossover design in five young women to compare the effects of high-intensity interval exercise (HIE) (four 30-s "all-out" sprints with 4.5 min of active recovery) and 30min continuous cycling with moderate-intensity continuous exercise (MOD) on GH secretion.…”
Section: Introductionmentioning
confidence: 99%